2005
DOI: 10.1002/j.2161-1874.2005.tb00003.x
|View full text |Cite
|
Sign up to set email alerts
|

The SASSI‐3 Face Valid Other Drugs Scale: A Psychometric Investigation

Abstract: The authors investigated the psychometric capabilities of the Face Valid Other Drugs (FVOD) scale of the Substance Abuse Subtle Screening Inventory‐3 (SASSI‐3; G. A. Miller, 1999). Internal consistency reliability estimates and construct validity factor analysis for 230 college students provided initial support for the psychometric properties of the SASSI‐3's FVOD scale.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…The SASSI‐3 is the most frequently used commercial screening instrument among master addictions counselors (Juhnke, Vacc, Curtis, Coll, & Paredes, 2003). The SASSI‐3 publication manual and subsequent psychometric research studies (Burck, Laux, Baker, Cochrane, & Ritchie, 2008; Burck, Laux, Harper, & Ritchie, 2010; Laux, Perera‐Diltz, Smirnoff, & Salyers, 2005; Laux, Salyers, & Bandfield, 2007; Laux, Salyers, & Kotova, 2005; Wright, Piazza, & Laux, 2008) reported SASSI‐3 reliability and validity estimates that exceeded those produced by instruments designed to measure the same constructs. However, debate has arisen regarding the SASSI‐3's criterion‐related validity in general as well as the utility of the instrument's subtle scales (Feldstein & Miller, 2007; Lazowski & Miller, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The SASSI‐3 is the most frequently used commercial screening instrument among master addictions counselors (Juhnke, Vacc, Curtis, Coll, & Paredes, 2003). The SASSI‐3 publication manual and subsequent psychometric research studies (Burck, Laux, Baker, Cochrane, & Ritchie, 2008; Burck, Laux, Harper, & Ritchie, 2010; Laux, Perera‐Diltz, Smirnoff, & Salyers, 2005; Laux, Salyers, & Bandfield, 2007; Laux, Salyers, & Kotova, 2005; Wright, Piazza, & Laux, 2008) reported SASSI‐3 reliability and validity estimates that exceeded those produced by instruments designed to measure the same constructs. However, debate has arisen regarding the SASSI‐3's criterion‐related validity in general as well as the utility of the instrument's subtle scales (Feldstein & Miller, 2007; Lazowski & Miller, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…G. Miller and Lazowski (1999) in the SASSI‐3 manual. However, the factor structure of two of the SASSI‐3's scales, the Face Valid Alcohol (FVA) scale and the Face Valid Other Drugs (FVOD) scale, did concur with the SASSI‐3 manual's data regarding these two scales (Laux, Perera‐Diltz, et al, 2005; Laux, Salyers, & Kotova, 2005). Finally, the SASSI‐3 manual reports high overall accuracy, sensitivity, and specificity rates when comparing the SASSI‐3's classification results to a substance dependence diagnosis using the Diagnostic and Statistical Manual of Mental Disorders (4th ed., text rev.…”
Section: Sassi‐3 Psychometric Reporting Conflictsmentioning
confidence: 88%
“…G. Miller & Lazowski, 1999). The SASSI‐3's psychometric properties have been studied by several independent researchers (Arneth, Bogner, Corrigan, & Schmidt, 2001; Clements, 2002; Feldstein & Miller, 2007; Gray, 2001; Laux, Perera‐Diltz, Smirnoff, & Salyers, 2005; Laux, Salyers, & Kotova, 2005; Lazowski, Miller, Boye, & Miller, 1998; Peters et al, 2000; Svanum & McGrew, 1995) and have been found to differ, at times significantly, from those reported in the SASSI‐3 manual (F. G. Miller & Lazowski, 1999).…”
Section: Sassi‐3 Psychometric Reporting Conflictsmentioning
confidence: 99%
“…The SASSI‐3 has 67 true/false questions that comprise the Symptoms (SYM), Obvious Attributes (OAT), Subtle Attributes (SAT), Defensiveness (DEF), Supplemental Addiction Measure (SAM), Family Versus Control Subjects (FAM), Correctional (COR) and Random Answering Pattern (RAP) scales. The back side of the instrument contains two subscales, the 12‐item Face Valid Alcohol (FVA) and 14‐item Face Valid Other Drugs (FVOD) subscales (Laux, Perera‐Diltz, Smirnoff, & Salyers, ; Laux, Salyers, & Kotova, ). The SASSI‐3 is highly accurate, sensitive, and specific (all 94%), with low false positive and false negative rates (both 6%; Miller & Lazowski, ).…”
Section: Methodsmentioning
confidence: 99%